P‐110: Efficient InP‐based Quantum Dot Light Emitting Diodes utilizing a Crosslinkable Hole Transport Layer. Issue 1 (30th May 2018) - Kim, Yohan; Heyne, Benjamin; Geßner, André; Park, Yongwook; Kang, Moonsung; Ahn, Seonhong; Lee, Bumsung; Wedel, Armin
Abstract : We demonstrate efficient InP‐based quantum dot (QD) LEDs utilizing a crosslinkable hole transport layers (HTL). The developed HTL exhibit great solvent resistance and smooth surface roughness. The influence of QD design, HTL structure as well as the corresponding processing of these materials on device performance was investigated.